Long-term aging trajectories of the accumulation of disease burden as predictors of daily affect dynamics and stressor reactivity - Gerstorf, Denis; Schilling, Oliver; Pauly, Theresa; Katzorreck, Martin; Lücke, Anna J.; Wahl, Hans-Werner; Kunzmann, Ute; Hoppmann, Christiane A.; Ram, Nilam (Psychology and aging, 2023)
Multiple-timescale studies provide new opportunities to examine how developmental processes that evolve at different cadences are intertwined. Developmental theories of emotion regulation suggest that the long-term, slowly evolving age-related accumulation of disease burden should shape short-term, faster evolving (daily) affective experiences. To empirically examine this proposition, we combined data from 123 old adults (65-69 years, 47% women) and 32 very old adults (85-88 years, 59% women) who provided 20 + year within-person longitudinal data on physician-rated morbidity and subsequently also completed repeated daily-life assessments of stress and affect six times a day over 7 consecutive days as they were going about their daily-life routines. Results from models that simultaneously articulate growth and intraindividual variability processes (in a dynamic structural equation modeling framework) revealed that individual differences in long-term aging trajectories of the accumulation of disease burden were indeed predictive of differences in three facets of affective dynamics that manifest in everyday life. In particular—over and above mean levels of disease burden—older adults whose disease burden had increased more over the past 20 years had higher base level of negative affect in their daily lives, more emotional reactivity to the experience of daily stressors, and more moment-to-moment fluctuations in negative affect that was unrelated to stressors (affective systemic noise). We highlight that developmental processes evolving over vastly different timescales are intertwined, and speculate how new knowledge about those relations can inform developmental theories of emotion regulation and daily-life functioning. (PsycInfo Database Record (c) 2023 APA, all rights reserved)